An improved synthesis of pennogenin. Issue 12 (22nd March 2019) - Gao, Ran; Shi, Yong; Tian, Wei-Sheng
Abstract: An improved synthesis of pennogenin, a bioactive component of Chinese herb "Chonglou" ( Paris ), is described. A ring-switching process opened the ring E of diosgenin and allowed the use of a hydroxyl-directed diboration/oxidation to introduce C17α-OH, hence eliminating the use of OsO4 . This strategy might be rendered to synthesize similar steroids with C17α-OH. Graphical abstract: Image 1